2017
DOI: 10.14486/intjscs670
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Referee Bias against College Football Programs from Historically Black Colleges and Universities

Abstract: The central objective of this investigation was to examine within game penalties that were levied against football programs from historically black colleges and universities (HBCUs) in the United States. Previous scholarship that sets an appropriate background on sports science and culture has revealed that referee bias has occurred in many European sports. It was in the methods section of this scholarship that statistical analyses were discussed in terms of game day penalties that occurred within the Football… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
4
6
0
Order By: Relevance
“…The most notable practical implication from this Division I study was evidence of disproportionate foul calling against HBCU men's college basketball teams. This finding supports a welldeveloped line of sports research that has found that referees call more penalties against HBCU football teams in comparison to PWI football teams (Dix, 2017), found that umpires call more walks per nine innings when the pitcher played for an HBCU relative to when the pitcher played for a PWI (Dix, 2020a), and found that referees call more personal fouls against Division I HBCU women's college basketball teams relative to PWI Division I women's college basketball teams (Dix, 2019). Referees have excessively penalized the in-game sociological behaviors of HBCU sports teams in the field of play.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The most notable practical implication from this Division I study was evidence of disproportionate foul calling against HBCU men's college basketball teams. This finding supports a welldeveloped line of sports research that has found that referees call more penalties against HBCU football teams in comparison to PWI football teams (Dix, 2017), found that umpires call more walks per nine innings when the pitcher played for an HBCU relative to when the pitcher played for a PWI (Dix, 2020a), and found that referees call more personal fouls against Division I HBCU women's college basketball teams relative to PWI Division I women's college basketball teams (Dix, 2019). Referees have excessively penalized the in-game sociological behaviors of HBCU sports teams in the field of play.…”
Section: Discussionsupporting
confidence: 87%
“…There are numerous reasons why this newest iteration of HBCU referee bias transpired in men's college basketball. The majority of the reasons why HBCU men's college basketball teams were disproportionately penalized in comparison to PWI men's college basketball teams are consistent with the conclusions noted in the previous sports science research of Dix (2017Dix ( , 2019Dix ( , 2020aDix ( , 2020b. For example, it is likely that HBCU men's college basketball teams were called for more PFPG than PWI men's college basketball teams due to (a) payback calls for overstated nonverbal behaviors, (b) a different style of aggressive play at HBCUs relative to PWIs, (c) implicit racial bias among some rogue referees, (d) fewer resources existing for HBCUs relative to PWIs, and (e) an inflated number of academic progress rate (APR) sanctions being levied against HBCUs, which includes limited practice time.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations